Gross Motor Function in Children with Congenital Zika Syndrome - Takahasi, Eliana Harumi Morioka; Alves, Maria Teresa Seabra Soares de Britto; Ribeiro, Marizélia Rodrigues Costa; Souza, Valéria Ferreira Pereira; Simões, Vanda Maria Ferreira; Borges, Marcella Costa Ribeiro; Amaral, Gláucio Andrade; Gomes, Lillian Nunes; Khouri, Ricardo; da Silva Sousa, Patricia; Silva, Antônio Augusto Moura da (Neuropediatrics, 2020)
Background Little information on gross motor function of congenital Zika syndrome (CZS) children is available.Objectives To evaluate gross motor function in CZS children aged up to 3 years, and its associated factors and changes in a minimum interval of 6 months.Methods One hundred children with CZS and cerebral palsy (36 with confirmed and 64 with presumed CZS) were evaluated with the Gross Motor Function Classification System (GMFCS) and Gross Motor Function Measure (GMFM-88/GMFM-66). Forty-six were reevaluated. Wilcoxon tests, Wilcoxon tests for paired samples, percentile scores, and score changes were performed.Results Clinical and socioeconomic characteristics (except maternal age), GMFM scores and GMFCS classification of confirmed and probable cases, which were analyzed together, were similar. The mean age was 25.6 months (±5.5); the median GMFM-88 score was 8.0 (5.4–10.8); and the median GMFM-66 score was 20.5 (14.8–23.1); 89% were classified as GMFCS level V. Low economic class, microcephaly at birth, epilepsy, and brain parenchymal volume loss were associated with low GMFM-66 scores. The median GMFM-66 percentile score was 40 (20–55). On the second assessment, the GMFM-66 scores in two GMFCS level I children and one GMFCS level IV child improved significantly. In one GMFCS level III child, one GMFCS level IV child, and the group of GMFCS level V children, no significant changes were observed.Conclusions Almost all CZS children had severe cerebral palsy; in the third year of life, most presented no improvement in gross motor function and were likely approaching their maximal gross motor function potential.
Keywords: Zika virus; cerebral palsy; nervous system; malformations